Proxima [videorecording (DVD)] - Winocour, Alice, 1976-; Green, Eva, 1980-; Dillon, Matt; Boulant-Lemesle, Zélie; Eidinger, Lars, 1976- (Vertical Entertainment, 2020)
Sarah is a French astronaut training at the European Space Agency in Cologne. She is the only woman in the arduous program. She lives alone with Stella, her seven-year-old daughter. Sarah feels guilty that she cannot spend more time with her child. When Sarah is chosen to be part of the crew of a year-long space mission called "Proxima", it creates chaos in the mother-daughter relationship.